Performance study of proximity coupled stacked configuration for wideband microstrip antenna - Rasin, Zulhani (2007)
This project started by identifying two main disadvantages of the typical microstrip antenna that are the low gain and narrow bandwidth. These two major drawbacks have limited its application despite of other advantages as compared to the conventional antenna. With the purpose of designing a wideband microstrip antenna, the two already proven bandwidth enhancement techniques; the patch stack configuration and coplanar parasitic patch was studied. Several antenna configurations were proposed and from the simulation result, the antenna bandwidth was improved from the typical 8 ~ 9 % up to 36 % by using these two techniques using a simple coaxial probe feeding without any matching network. Actual fabrication was also carried out and several measurements were conducts to verify its performance. The measurement results, even not fully conform to the simulation result, has proven the effectiveness of the above mentioned bandwidth enhancement techniques.